African Mole-Rats May Have High Bone Conduction Sensitivity to Counterbalance Low Air Conduction Sensitivity - Andrew Bell (Audiology Research)
Background/Objectives: Subterranean mole-rats live in an intricate system of underground tunnels, a unique acoustic environment that has led to adaptations to their hearing. Most experimenters have concluded that mole-rats have poor hearing thresholds, perhaps 20–40 dB less sensitive than rodents living on the surface. The potential problem identified here is that mole-rat thresholds have all been measured in air, whereas there is some evidence—theoretical and observational—to suggest that these animals may hear more sensitively via bone conduction. Methods: A wide-ranging review of the literature surrounding mole-rat hearing is undertaken and then interpreted in terms of the ways air conduction and bone conduction thresholds are measured. The important factor, often overlooked, is that the detection of an acoustic signal is most sensitive when there are matching impedances all along the transmission path, and the argument is made that, for subterranean mole-rats, more energy may be transmitted to their cochlea when the head is directly in contact with the earth than when an acoustic signal must propagate from the earth to the air and then reach the cochlea via the external and middle ear. Results: Based on observational evidence, theoretical considerations, and inferences from related species, the suggestion is made that, for African mole-rats, high bone conduction sensitivity could make up for their relatively poor air conduction thresholds. Conclusions: Bone conduction audiograms are needed for mole-rats, similar to those for other animals sensitive to substrate vibration such as snakes or amphibians. It is possible that the hearing thresholds of mole-rats may, when measured appropriately, be comparable to those of other rodents.